Dwellers a novel - Victoria, Eliza 1986- (Tuttle Publishing, 2022)
"This dark fantasy is sure to take your breath away. The rules are strict and absolute: Rule No. 1: Don't kill the body you inhabit. Rule No. 2: Never mention your previous name again. Rule No. 3: Don't talk about your previous life. Ever. But what happens when, in escaping your old life by stealing a new one, you jump out of the frying pan and into the fire? Cousins from a clan of "dwellers"-people who inhabit the bodies and lives of others-become brothers when they take over the bodies of Jonah and Louis. An injury forces them to remain in the brothers' house, where they discover that the basement holds a dead body! As old and new secrets come to light, it becomes clear there is no such thing as actions without consequences. Fans of Richard Morgan, Adam Silvera, and Blake Crouch's speculative fiction will adore Eliza Victoria's action-packed supernatural mystery. Winner of the Philippine National Book Award, Dwellers is the urban fantasy novel that you won't want to miss!"--